Tradisi Bapingit Menjelang Pernikahan dalam Realitas Sosial dan Gender Masyarakat Adat Banjar - Azizah, Azizah (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2025)
The research examines the tradition of bapingit before marriage in the Banjar indigenous community with a focus on social construction and the dynamics of gender roles. The bapingit tradition is a form of local wisdom passed down from generation to generation, which aims to educate and prepare the bride and groom physically, mentally and spiritually before entering married life. However, in its development the tradition is the only imposed on women with social pressure to maintain morality and honor, while men do not undergo similar rituals and have a more passive role. This study aims to answer the implementation of the bapingit tradition and the social and gender construction in the bapingit tradition of the Banjar indigenous community, using empirical research and a legal sociological approach. Data collection techniques through interviews and observations were analyzed using ‘urf, maslahah, and structural functionalism theory, as well as gender equality theory. The result of this research is that bapingit in Banjar customary society is not just a cultural heritage, but also has a philosophical basis and benefits as a form of guarding the bride and groom who are in line with ‘urf theory and maslahah theory. The results of this study show that social construction has led to changes in the parrern of implementation of the bapingit tradition that reflects gender stereotypes that place women as guardians of traditional values and morals, thus reinforcing unequal gender roles in Banjar society